2001
DOI: 10.1002/ijc.1582
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of 9D7, a novel human protein overexpressed in renal cell carcinoma

Abstract: With the objective of discovering novel tumor-associated antigens of the cancer/testis type, we compared the transcriptional profiles of renal cell carcinoma (RCC) and nontumorous kidney and further screened for genes expressed in RCC and testis, but not other normal tissues. In a first step, a representational difference analysis library consisting of approximately 1,900 RCC cDNA clones was generated. Clones were then spotted onto filters and hybridized with cDNA probes derived from a testis-specific cDNA lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…5B). Overexpression of EGLN3 in RCCs was also confirmed by immunohistochemistry (20). Four additional genes, NDGR1, OSF-2, TP73L, and NAT1 were verified in the same way, all exhibiting high agreement between microarray and real-time PCR results.…”
Section: Tissue-wide Profiling and Tumor-specific Genesmentioning
confidence: 56%
See 1 more Smart Citation
“…5B). Overexpression of EGLN3 in RCCs was also confirmed by immunohistochemistry (20). Four additional genes, NDGR1, OSF-2, TP73L, and NAT1 were verified in the same way, all exhibiting high agreement between microarray and real-time PCR results.…”
Section: Tissue-wide Profiling and Tumor-specific Genesmentioning
confidence: 56%
“…Thus far, two splice variants have been demonstrated for EGLN3 (formerly described as 9D7), which recently has been shown to be involved in the regulation of the hypoxia-inducible factor (20,21). By RT-PCR studies using RNA samples derived from normal tissues and tumor samples, we demonstrated that the shorter splice variant is dominant over the longer one in all tissues.…”
Section: Tissue-wide Profiling and Tumor-specific Genesmentioning
confidence: 79%
“…[41][42][43] Recently, systematic searches for novel tumour antigens of RCC on the basis of their tumour-specific transcriptional profiles have also been performed. Transcriptomes of tumours and normal tissues were assessed by either representational difference analysis (RDA) 44,45 or by microarray technology. 32,[46][47][48][49] More than 1,700 differentially expressed genes/cDNAs have been detected.…”
Section: Identification Of Novel Rcc-associated Genes By Transcriptommentioning
confidence: 99%
“…32,[46][47][48][49] Furthermore, 9D7 was identified as a novel gene over-expressed in RCC as well as in other cancers. 45 Besides the differential expression pattern of tumour versus normal cells, there exists a significant distinction in the gene expression profile of tumours obtained from patients with a relatively nonaggressive, compared with a relatively aggressive, form of disease, 47 and of tumours with distinct subtypes. Thus, transcription profiling is a powerful tool for monitoring patients' tumours; this may also have an impact on cancer diagnosis and prognosis and, consequently, on the mode of therapy selected.…”
Section: Identification Of Novel Rcc-associated Genes By Transcriptommentioning
confidence: 99%
See 1 more Smart Citation